PASSED: Brain atrophy in non-demented individuals in a long-term longitudinal study from two independent cohorts - Haas, Anna-Lena; Olm, Pauline; Utz, Janine; Siegmann, Eva-Maria; Spitzer, Philipp; Florvaag, Anna; Schmidt, Manuel Alexander; Doerfler, Arnd; Lewczuk, Piotr; Kornhuber, Johannes; Maler, Juan Manuel; Oberstein, Timo Jan; et al. (Frontiers in Aging Neuroscience, 2023)
Alzheimer´s disease (AD) is indicated by a decrease in amyloid beta 42 (Aβ42) level or the Aβ42/Aβ40 ratio, and by increased levels of phosphorylated Tau at Thr181 (pTau181) in cerebrospinal fluid (CSF) years before the onset of clinical symptoms. However, once only pTau181 or both Aβ and pTau181 are increased (PASSED), cognitive decline in individuals with subjective or mild cognitive impairment is slowed compared to individuals with AD, leading to the suggestion that this biomarker combination represents a distinct pathophysiological condition. In this study, we determined the longitudinal atrophy rates of AD, PASSED, and Biomarker-negative nondemented individuals of two independent cohorts to determine whether these groups can be distinguished by their longitudinal atrophy rates. Depending on their CSF-levels of pTau 181 (T), total Tau (N), Aβ42 or Aβ42/Aβ40 ratio (A), 185 subjects from the ADNI cohort and 68 subjects from the Erlangen AD cohort were assigned to an ATN group (A–T–N–, A–T+N±, A+T–N±, and A+T+N±) and underwent T1-weighted structural magnetic resonance imaging (MRI). Longitudinal grey matter atrophy patterns were assessed with voxel-based morphometry (VBM) using the cat12 toolbox on spm12 of MRI scans from individuals in the ADNI cohort with a mean follow-up of two and five years, respectively. The annualized atrophy rate for individuals in the Erlangen cohort was determined using region of interest analysis (ROI) in terms of a confirmatory analysis. In the A–T+N± group, VBM did not identify any brain region that showed greater longitudinal atrophy than the A+T+N±, A+T–N± or control group. In contrast, A+T+N± subjects showed marked longitudinal atrophy in the temporal lobe compared with A-T+N± and biomarker-negative subjects. The ROI in the angular gyrus identified by VBM analysis of the ADNI cohort did not discriminate better than the hippocampal volume and atrophy rate between AD and PASSED in the confirmatory analysis. In this study, nondemented subjects with increased pTau-levels without amyloidopathy and Aβ surge with subtle cognitive deterioration (PASSED) did not show a unique longitudinal atrophy pattern in comparison to nondemented subjects with AD. The nonsignificant atrophy rate compared with controls suggests that increased pTau181-levels without concomitant amyloidopathy did not indicate a neurodegenerative disorder.